Targeted Inhibition of miR-221/222 Promotes Cell Sensitivity to Cisplatin in Triple-Negative Breast Cancer MDA-MB-231 Cells - Li, Shujun; Li, Qun; Lü, Jinhui; Zhao, Qian; Li, Danni; Shen, Lei; Wang, Zhongrui; Liu, Junjun; Xie, Dongping; Cho, William C.; Xu, Shaohua; Yu, Zuoren (Frontiers in Genetics, 2020)
Cisplatin has been widely used in treatment of a various types of cancer including triple negative breast cancer (TNBC) by damaging DNA and inducing apoptosis. However, its anti-cancer effects are often limited due to chemo resistance, which is one of main reasons causing cancer relapse and metastasis. To overcome resistance, cisplatin is often used in combination with other drugs or molecules. Herein, targeted inhibition of miR-221/222 in MDA-MB-231 cells promoted cisplatin-induced cell apoptosis, and increased the cell sensitivity to cisplatin in vitro. A much higher expression of miR-221/222 was detected in cisplatin-resistant TNBC cells, as well as cisplatin-resistant breast cancer patients. The combination chemotherapy of cisplatin with anti-miR-221/222 showed much higher efficiency in suppressing tumor growth in the mice model carrying TNBC tumors in vivo. In addition, miR-221 and miR-222 showed synergetic effects on regulating sensitivity to cisplatin in TNBC cells. Suppression of socs1-stat3-bcl2 pathway and activation of p53-pten signaling both contribute to anti-miR-221/222-induced sensitivity to cisplatin in MDA-MB-231 cells. These findings suggest the potential of a novel approach for combination chemotherapy of cisplatin with small non-coding RNA in treatment of human TNBC.